2016
DOI: 10.1093/jxb/erw294
|View full text |Cite
|
Sign up to set email alerts
|

The role of Arabidopsis Actin-Related Protein 3 in amyloplast sedimentation and polar auxin transport in root gravitropism

Abstract: HighlightArabidopsis actin-related protein ARP3 plays a role in amyloplast sedimentation and polar auxin redistribution during root gravitropism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 84 publications
(128 reference statements)
1
29
0
Order By: Relevance
“…This last hypothesis is supported by studies using actin inhibitors or actin mutants showing a decrease of saltation motion in Arabidopsis thaliana stems ( 14 , 17 ). However, disrupting actin also decreases the cytoplasm viscosity and speeds up the diffusion of statoliths in other systems (roots) ( 18 , 23 ), making the interpretation of these mutant or drug-based experiments difficult.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This last hypothesis is supported by studies using actin inhibitors or actin mutants showing a decrease of saltation motion in Arabidopsis thaliana stems ( 14 , 17 ). However, disrupting actin also decreases the cytoplasm viscosity and speeds up the diffusion of statoliths in other systems (roots) ( 18 , 23 ), making the interpretation of these mutant or drug-based experiments difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments using actin inhibitors and mutants inducing a fragmentation of AFs also reported a reduction of the saltatory motion of statoliths ( 17 ), suggesting a key role of actin in statolith agitation. However, actin inhibitors also decrease the cytoskeleton viscosity, making statoliths more mobile ( 18 , 23 ). Our study shows that it is possible to disentangle both effects.…”
Section: Discussionmentioning
confidence: 99%
“…The sgr9 mutant of Arabidopsis exhibited reduced stem gravitropism and amyloplast sedimentation because of denser network of actin filaments enmeshed amyloplasts and reduced their normal sedimentation (Nakamura et al, 2011). In central columella cells of Arabidopsis root it was also found that ARP3 mutants display thick actin bundles surrounding amyloplasts that possibly affect amyloplast kinetics, indicating that actin cytoskeleton may regulate amyloplast movement through regulating local viscosity of the cells (Zou et al, 2016). However, the intracellular environments in shoot and root endodermal cells differ considerably (Blancaflor, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several papers also indicated that actin in the cytoskeleton has a significant role in gravity signaling, as pressure exerted by sedimentation of statoliths on actin polymers could conduct a physical pressure signal toward the plasma membrane or ER membrane, causing ion channels to open (Yoder et al, 2001;Perbal and Driss-Ecole, 2003). Additionally, the ARP3 subunit of the Actin-Related Protein 2/3 (ARP2/3) complex is involved in regulating amyloplast sedimentation kinetics, as Arabidopsis distorted1 (dis1) mutants lacking ARP3 display a delayed response to gravitropic stimulation (Zou et al, 2016). However, the exact role of the cytoskeleton deserves more attention, as pharmacological experiments gave contradictory results, showing both inhibition and promotion of gravitropism (Ma and Hasenstein, 2006;Blancaflor, 2013).…”
Section: Gravitropismmentioning
confidence: 99%